Anticoagulation knowledge assessment in unprivileged people of Baluchistan - Khuzaima Tariq; Usman Ahmad; Maheen Sheikh (Journal of the Pakistan Medical Association)
The descriptive, cross-sectional study was planned to assess patients' knowledge on warfarin usage at a newly-developed health facility in Quetta, Pakistan. Warfarin knowledge and anticoagulant control was assessed using the pre-validated 29-item Anticoagulation Knowledge Assessment questionnaire which was dispensed during face-to-face interviews. Each question carried 3.45 points, and a minimum of 21 correct answers (21*3.45=72.4%) was the cut-off score. Data was analysed using SPSS 27. Of the 37 patients, 23(62.1%) were females, and 16(43%) were aged 31-40 years. Mechanical mitral valve replacement 9(24.3%) and mitral stenosis with atrial fibrillation 8(21.6%) were the main grounds for warfarin use. The awareness cut-off score was met by 4(10.8%) patients. The international normalised ratio, assessed using Jonckheere-Terpstra test, had no significant association with education level (p=0.380) or awareness score (p=0.102). The knowledge level among warfarin users was found to be poor. Effective policies are needed to identify hindrances and remove them to improve awareness levels.